If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(1 + -3n) = 3n + 63 (1 * 3 + -3n * 3) = 3n + 63 (3 + -9n) = 3n + 63 Reorder the terms: 3 + -9n = 63 + 3n Solving 3 + -9n = 63 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. 3 + -9n + -3n = 63 + 3n + -3n Combine like terms: -9n + -3n = -12n 3 + -12n = 63 + 3n + -3n Combine like terms: 3n + -3n = 0 3 + -12n = 63 + 0 3 + -12n = 63 Add '-3' to each side of the equation. 3 + -3 + -12n = 63 + -3 Combine like terms: 3 + -3 = 0 0 + -12n = 63 + -3 -12n = 63 + -3 Combine like terms: 63 + -3 = 60 -12n = 60 Divide each side by '-12'. n = -5 Simplifying n = -5
| g(x)=(x+2)-4 | | xy+3=y | | x+2y=3xy | | xy+y=1 | | 12x+6y=18 | | -2x-9=9 | | 6(3x-2)+4x= | | 5(y+6)+4= | | 2x+15=8x+8 | | 6x+16=21 | | 9m-3=-39+3m | | 6(x-1)+4=3(7x+1) | | 5(2t-3)+4t=30-t | | 4y-3=0+y | | 15x^2-34x+15= | | (-3)-(2)= | | 5p+3=4p+6 | | 20p-2p+4p=20p-6p | | -17x-20=14x+70 | | -4x-11x=-75 | | 2.5x+3=15-1.5x | | 2x+1=4x-15 | | 2x-7=x+6 | | 17-5x=9+3x | | 5x+9=2x+30 | | 2x^2-x+6=0 | | 4x^2-44x+96= | | 7x-1=4x-3 | | 4x+0.2=6.6 | | 5x+4-4x=12-29 | | n^2-n+4=0 | | 5x-11-4x=-5 |